The HoxB1 hexapeptide is a prefolded domain: Implications for the Pbx1/Hox interaction - Slupsky, Carolyn M. (Cold Spring Harbor Laboratory Press, 2001)
Hox proteins are transcriptional regulators that bind consensus DNA sequences. The DNA-binding specificity of many of these Hox proteins is modulated by the heterodimerization with partners, such as the Pbx proteins. This cooperative heterodimerization is accomplished through a conserved hexapeptide motif found N-terminal to the Hox DNA-binding homeodomain. Several human leukemias have been associated with a chromosomal translocation involving either the Hox gene (i.e., NUP98/HOXA9) or the gene encoding Pbx1 (E2A/PBX1). The transforming ability of these fusion oncoproteins relies at least partially on the ability to interact with one another through this hexapeptide motif. Herein we describe NMR structural calculations of the hexapeptide of HoxB1 (Nα-acetyl-Thr-Phe-Asp-Trp-Met-Lys-amide) that has been shown to mediate binding between HoxB1 and Pbx1 and a hexapeptide consensus sequence (Nα-acetyl-Leu-Phe-Pro-Trp-Met-Arg-amide). The consensus peptide exists in two conformations caused by cis–trans isomerization of the Phe–Pro peptide bond. The structures of the HoxB1 peptide and the trans form of the consensus peptide reveal a turn very similar to that found as part of the HoxB1/Pbx1/DNA complex in the X-ray crystal structure. This observation implies that this region is at least partially ′preformed' and thus ready to interact with Pbx1 and stabilize binding of Pbx1 and HoxB1 to DNA. The structural results presented here provide a starting point for synthesizing potential nonpeptide or cyclical peptide antagonists that mimic the interaction of these transcriptional cofactors resulting in a potential chemotherapeutic for certain types of leukemias.